Fundamental Solution in the Theory of Thermomicrostretch Elastic Diffusive Solids. (17th May 2011) - Kumar, Rajneesh; Kansal, Tarun
Abstract : We construct the fundamental solution of system of differential equations in the theory of thermomicrostretch elastic diffusive solids in case of steady oscillations in terms of elementary functions. Some basic properties of the fundamental solution are established. Some special cases are also discussed.